Testing the Modigliani-Miller theorem directly in the lab - M. Vittoria Levati; Jianying Qiu; Prashanth Mahagaonkar (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2011)
We present an experiment designed to test the Modigliani-Miller theorem. Applying a general equilibrium approach and not allowing for arbitrage among firms with different capital structures, we find that, in accordance with the theorem, participants well recognize changes in the systematic risk of equity associated with increasing leverage and, accordingly, demand higher rate of return. Yet, this adjustment is not perfect: subjects underestimate the systematic risk of low-leveraged equity whereas they overestimate the systematic risk of high-leveraged equity, resulting in a U-shaped cost of capital. A (control) individual decision-making experiment, eliciting several points on individual demand and supply curves for shares, provides some support for the theorem.
Keywords: G32; C91; G12; D53; 330; Modigliani-Miller theorem; experiments; decision making under risk; general equilibrium; Kapitalstrukturtheorie; Entscheidung bei Unsicherheit; Test; Allgemeines Gleichgewicht